Serverless Computing : Benefits and challenges - Drozdová, Zuzana; Feuerlicht, Jiří; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
Serverless computing is a relatively new, and still evolving Cloud category, which brings a new approach to the development and deployment of applications. The Serverless fundamental model Function as a Service (FaaS) allows to execute small pieces of code, without dealing with a server. The purpose of this thesis is to explore this topic more deeply, and introduce architectural design patterns, which are suitable for the Serverless approach. This cloud category has benefits, but as it is a new technology, it has also certain drawbacks. This thesis demonstrates these benefits and drawbacks on use cases, or a situation. The purpose of the practical part is to develop a prototype application, which applies the architectural patterns described in the thesis. In the thesis is also described a detailed implementation and then evaluation of the application. The result of this thesis are benefits and drawbacks of Serverless computing, Serverless Architectural Design Patterns and a prototype application.
Vedoucí práce: Jiří Feuerlicht
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses